Thermal and magnetic anomalies of α-iron: an exploration by extended x-ray absorption fine structure spectroscopy and synchrotron x-ray diffraction. (7th July 2016) - Boccato, Silvia; Sanson, Andrea; Kantor, Innokenty; Mathon, Olivier; Dyadkin, Vadim; Chernyshov, Dmitry; Carnera, Alberto; Pascarelli, Sakura
Abstract: The local structure and dynamics of α -iron have been investigated by extended x-ray absorption fine structure (EXAFS) spectroscopy and x-ray diffraction (XRD) in order to shed light on some thermal and magnetic anomalies observed in the last decades. The quantitative EXAFS analysis of the first two coordination shells reveals a peculiar local vibrational dynamics of α -iron: the second neighbor distance exhibits anharmonicity and vibrational anisotropy larger than the first neighbor distance. We search for possible distortions of the bcc structure to justify the unexplained magnetostriction anomalies of α -iron and provide a value for the maximum dislocation of the central Fe atom. No thermal anomalies have been detected from the current XRD data. On the contrary, an intriguing thermal anomaly at about 150 K, ascribed to a stiffening of the Fe–Fe bonds, was found by EXAFS.